2020
DOI: 10.52166/inspiramatika.v6i1.1922
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kecemasan Matematika Dan Prokrastinasi Akademik Siswa Terhadap Hasil Belajar Matematika Siswa Kelas Viii SMP Negeri 7 Balikpapan

Abstract: The existence of students' negative views on mathematics causes anxiety and procrastination. This study aims to determine the effect of mathematical anxiety and academic procrastination on mathematics learning outcomes in class VIII SMP Negeri 7 Balikpapan. The research approach used is a quantitative approach with survey method. The population in this study were all eighth grade students of SMP Negeri 7 Balikpapan, as many as 362 students and a total sample of 72 students. The sampling technique uses cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
0
1
Order By: Relevance
“…This shows that there are still many other factors or variables that influence the variables studied, both from outside the discipline and from factors within the discipline itself. This is different from the research by Zuraidah et al (2020) on the relationship between math anxiety and academic procrastination on students' learning achievement, which explains that students' math learning achievement tends to increase as math anxiety and academic procrastination decrease. The most likely reason for the lack of correlation between these variables is that the indicators used do not adequately describe the variables being studied.…”
Section: Figure 2 Results Of Person Maps Output Table Academic Procra...contrasting
confidence: 89%
“…This shows that there are still many other factors or variables that influence the variables studied, both from outside the discipline and from factors within the discipline itself. This is different from the research by Zuraidah et al (2020) on the relationship between math anxiety and academic procrastination on students' learning achievement, which explains that students' math learning achievement tends to increase as math anxiety and academic procrastination decrease. The most likely reason for the lack of correlation between these variables is that the indicators used do not adequately describe the variables being studied.…”
Section: Figure 2 Results Of Person Maps Output Table Academic Procra...contrasting
confidence: 89%
“…The current study directly showed that students' anxiety affected students' learning outcomes. It was a further research supporting the previous studies which also discovered the same findings (Juliyanti & Pujiastuti, 2020;Zuraidah et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Mathematic anxiety is classified as an individual psychology or emotional factor influencing their selfefficacy, self-confidence, and learning motivation (Giriansyah & Pujiastuti, 2021;Kodirun et al, 2019). There is study that view anxiety as an obstacle in learning process disturbing the students' cognitive function in concentrating, remembering, and forming the concept to solve the problem (Zuraidah et al, 2020). It is added that the higher anxiety than the worse reaction frequently appears in the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil belajar adalah kemampuan-kemampuan yang dipunyai oleh siswa sesudah mengalami pengalaman belajar. Hasil belajar tersebut mendeskripsikan pencapaian yang telah dicapai oleh siswa dari tujuan pembelajaran pada tingkatan tertentu yang ditunjukkan dengan nilai tes angka/huruf (Nurfa, 2020). Selain itu, hasil5belajar merupakan5hasil dari proses interaksi5antar tindak5belajar dan tindak5mengajar (Mangelep, Tiwow, et al, 2023).…”
Section: Pendahuluanunclassified